2007
DOI: 10.1055/s-2007-964849
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Endurance and Explosive Type Strength Training Improves Neuromuscular and Anaerobic Characteristics in Young Distance Runners

Abstract: To study effects of concurrent explosive strength and endurance training on aerobic and anaerobic performance and neuromuscular characteristics, 13 experimental (E) and 12 control (C) young (16 - 18 years) distance runners trained for eight weeks with the same total training volume but 19% of the endurance training in E was replaced by explosive training. Maximal speed of maximal anaerobic running test and 30-m speed improved in E by 3.0 +/- 2.0% (p < 0.01) and by 1.1 +/- 1.3% (p < 0.05), respectively. Maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 36 publications
6
113
1
11
Order By: Relevance
“…Posteriormente, vários estudos utilizaram imagens obtidas por ultrassonografia 11,18,22 , ressonância magnética 8 e tomografia computadorizada 23 para análise das adaptações morfológicas. Especificamente, tratando-se da mensuração da EM por ultrassonografia, tem-se utilizado diferentes pontos de medida 10,17 . Sendo assim, identificar se há semelhança entre os valores de diferentes pontos de medida da EM, como também se estes valores têm correlação com a produção de força muscular, proporcionaria uma importante contribuição metodológica quando a ultrassonografia for utilizada como método de análise.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Posteriormente, vários estudos utilizaram imagens obtidas por ultrassonografia 11,18,22 , ressonância magnética 8 e tomografia computadorizada 23 para análise das adaptações morfológicas. Especificamente, tratando-se da mensuração da EM por ultrassonografia, tem-se utilizado diferentes pontos de medida 10,17 . Sendo assim, identificar se há semelhança entre os valores de diferentes pontos de medida da EM, como também se estes valores têm correlação com a produção de força muscular, proporcionaria uma importante contribuição metodológica quando a ultrassonografia for utilizada como método de análise.…”
Section: Resultsunclassified
“…Nesta perspectiva, a uniformidade dos pontos de medida da EM parece ter relevância quer em estudos transversais quer em estudos longitudinais que se utilizam desta variável. Como exemplo disso, têm sido identificadas na literatura adaptações morfológicas diferenciadas ao longo do músculo, em resposta a programas de treinamento, que avaliaram a EM por ultrassonografia 10,17,18 . Portanto, a comparação entre investigações que realizaram a ultrassonografia para avaliar alterações morfológicas musculares, bem como a QM, podem ser comprometidas, uma vez que diferentes pontos de medida da EM podem representar diferentes adaptações morfológicas e valores distintos de QM.…”
Section: Introductionunclassified
“…Although muscular strength does not directly influence the cardiorespiratory system, it has been suggested that an increase in muscular strength is related to movement economy (25,29), because stronger men can perform aerobic activity using a lower percentage of their strength, thus recruiting fewer type-II muscle fibers and so preferentially using fibers with a more oxidative metabolism that is more resistant to fatigue (8,16,25). In fact, in the present study, a negative correlation was found between relative muscular activation (%RMS) of the vastus lateralis during the cycle ergometer test and the 1RM, MVC, and RFD values.…”
Section: Discussionmentioning
confidence: 99%
“…En cualquier caso, hasta la fecha no está bien documentado que esas ganancias se traduzcan siempre en beneficios para el rendimiento en pruebas atléticas de resistencia (Rønnestad & Mujika, 2014). Aún menos claro está que las ganancias se puedan manifestar en mejoras de la capacidad aeróbica (VO 2max ) (Saunders et al, 2006;Mikkola et al, 2007Mikkola et al, , 2011Storen et al, 2008;Taipale et al, 2013).…”
Section: Discussionunclassified